Journalist of Print Mass Media in Medan Study: Journalism, Print Media of Newspaper Journalistic and Organizational Structure of Print Media - M. Yoserizal Saragih (Britain International for Academic Research (BIAR) Publisher, 2019)
The aim of this study is to determine the journalist of print mass media in Medan. This study is about journalism, print media of newspaper journalistic and organizational structure of print media. The work area of ​​journalists in Medan is public space, an area that is worthy of being known by the public or the public. Therefore, journalists are required to have the ability to reveal and inform a complete problem by upholding the values ​​of truth and justice and must be able to make themselves half diplomats, half detectives. This means that journalists must have skilled diplomacy skills, even though the way they work is similar to detectives. Mass media journalism is a tool used to convey messages from sources to the public using mechanical communication tools, such as newspapers, radio, television, films and so on. And in this case the mass media being referred to is print mass media. That newspapers are sheets published by the press which contain news, essays, writings, advertisements, and other journalistic products that are printed periodically, circulated, and sold in general, which function as social control tools that provide information both entertainment education and another thing for the community.